Emergence et développement des dispositifs d’accès au logement : quelle place pour les handicapés psychiques ? (Europe occidentale-Amérique du Nord, milieu du XIXe-début XXIe siècle) - Gwenaëlle Legoullon (Amnis)
In the 19th century, Western Europe and North America adopted the asylums model for treating, isolating and housing people considered insane. But criticism of this system grew and alternative experiments were tried. Formulas for accommodation and medical care outside the walls were diversified, but initially remained limited. The post-World War II period, marked by the rapid development of open hospitalization and the emergence of pioneering schemes aimed at integrating or reintegrating patients into the community (with their families, in their neighborhoods, etc.), favored the search for solutions to house some patients outside hospitals. But it was above all the reorganization of psychiatric care and the steady decline in the number of hospital beds that began in Western Europe and North America in the 1960s that accelerated the movement. The aim of this article is to examine the role played by the mentally ill, their families and the associative network in which all these players participate in the emergence and development of out-of-hospital housing between the middle of the 19th century and the beginning of the 21st century in Western Europe and North America. After presenting a brief overview of the first out-of-hospital housing projects, followed by public policies on housing for the mentally ill from the 1960s onwards, the paper turns to a number of case studies drawn from experiments carried out in France from the 1960s onwards.